Media discourse and the public sphere - Chouliaraki, Lilie (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In this paper, I am attempting to throw into relief significant aspects of the function of television debate as a public sphere. My working assumption is that public dialogue, including its televised versions, involves primarily the establishment of a meaning horizon which delimits what is to be said and known, and which authorises as true certain meanings and knowledges at the expense of others. Put differently, there is a ’politics of truth’ at play in every mediated debate which is central in the constitution of the debate as a public sphere. It is precisely this politics that I want to examine in this article. Using empirical material from a prime-time debate programme in Danish television, which is concerned with the right to privacy of public personalities, I analyse the forms of interactional control and dialogic organisation employed in the debate, so as to address the following questions: What are the communicative practices which confer upon the television debate genre the legitimacy of public debate? Which are the principles by which communication is regulated? Which are the domains of meaning construed by this regulation? And which is the potential for democratic deliberation released in these domains?